Correlation of tongue coating thickness with microinflammatory state and oral microbiome in maintenance hemodialysis patients - Yanqin Zhu; Xueyan Zeng; Aiping Zhang; Bin Lu; Mengqi Wu; Hong Liu; Fenggui Zhu; Riyang Lin (Journal of Oral Microbiology)
Aim This study investigated the correlation between tongue coating thickness (TCT), micro-inflammatory state (MIS), and oral microbiome in maintenance hemodialysis (MHD) patients.Methods Forty MHD patients (20 thin-tongue coating [BTZ], 20 thick-tongue coating [HTZ]) and 15 healthy controls (DZZ) were enrolled. Blood microinflammatory markers were analyzed in all patients. Saliva samples from 15 HTZ, 15 BTZ, and 15 DZZ underwent 16S rRNA sequencing.Results HTZ patients exhibited higher microinflammatory marker levels than BTZ. Oral microbiome species richness in DZZ surpassed that of the MHD groups, with distinct structural differences, particularly between HTZ and DZZ. HTZ showed higher abundances of Actinobacillus, Peptostreptococcus, and Lachnospiraceae NK4A136 group than BTZ. Correlation analysis revealed a positive correlation between the levels of IL-6 and TNF-α and the abundance of Fusobacterium, but a negative correlation with Streptococcus. Additionally, the TNF-α level positively correlated with Campylobacter.Conclusion Thick tongue coating in MHD patients is associated with elevated microinflammation and altered oral microbiome, suggesting a link between inflammation and microbial dysbiosis.